Reconciling the controversial data on the effects of C60 fullerene at the organismal and molecular levels using as a model Drosophila melanogaster. (August 2019) - Yasinskyi, Y.; O., Protsenko; O., Maistrenko; V., Rybalchenko; Prylutskyy, Yu.; Tauscher, E.; Ritter, U.; Kozeretska, I.
Highlights: C60 fullerene can induce DNA damage. C60 fullerene does not affect the reproductive system and embryogenesis. Activation of DNA-repair might decrease the effects of C60 fullerene at the organismal level. Abstract: Fullerenes have attracted attention since their discovery as structural units of complex carbon nanostructures capable of transporting drugs and macromolecules. As such artificial nanomaterials are applied in biology and medicine, they are routinely scrutinized for their effects on living organisms. The results of such studies range from direct destabilizing effects on DNA molecules to amelioration of the toxic effects of known genotoxic agents. We tested the effect of buckminsterfullerene (C60 ) on Drosophila melanogaster at DNA, tissue and organism levels. The water-soluble pristine C60 fullerene at the concentration of 20 μg/ml and 40 μg/ml leads to the activation of the mus209 gene in D. melanogaster larvae salivary glands, which can indicate higher levels of DNA damage. However, the absence of effects at the cell and organismal level could be explained by the activation of repair systems or by active elimination of damaged cells.